Effects of contemporary cryo-compression on post-training performance in elite academy footballers - Alexander, J.; Keegan, J.; Reedy, A.; Rhodes, D. (Biology of Sport, 2022)
Fatigue is a predisposing risk factor for injury commonly investigated in elite football populations. Little evidence advocates the most beneficial recovery strategies including contemporary cooling applications. The aim of the study was to examine immediate effects of the Game Ready® on physiological and biomechanical measures in a population of elite male academy footballers, following a fatiguing training session mid-competitive season. Twenty, elite male footballers took part (180.2 ± 8.7cm, 75.0 ± 11.4kg, 18 ± 0.5years). Following a normal fatiguing training session, players were randomly assigned to receive either cryotherapy (Game Ready®) (20-minutes at medium compression (5-55 mm Hg)) or passive recovery (PAS). Data was collected at matchday+1, immediately post-training and immediately post-intervention. Performance measures included countermovement jump (CMJ), isometric adductor strength (IAS), hamstring flexibility (HF), and skin surface temperature (Tsk). Significant main effects for group for CMJ data following exposure to cooling were displayed (p = < 0.05). Individual group analysis displayed a significant reduction in CMJ performance in the group exposed to cryotherapy (p = < 0.05) immediately post, but not for PAS. No main effects were identified for cryotherapy or PAS group for IAS or HF (p = > 0.05). Tsk reduced significantly (p = < 0.05) in the cryotherapy group, meeting therapeutic Tsk range. Reductions in performance immediately following exposure to pneumatic cryo-compressive devices may negate the justification of this recovery strategy if neuromuscular mechanisms are required in immediate short term. Application of such recovery strategies however are dependent on the type of recovery demand and should be adapted individually to suit the needs of the athlete to optimise readiness to train/play.